TLR7 and TLR3 Sense Brucella abortus RNA to Induce Proinflammatory Cytokine Production but They Are Dispensable for Host Control of Infection - Campos, Priscila C.; Gomes, Marco Túlio R.; Guimarães, Erika S.; Guimarães, Gabriela; Oliveira, Sergio C. (Frontiers in Immunology, 2017)
Brucella abortus is a Gram-negative, facultative intracellular bacterium that causes brucellosis, a worldwide zoonotic disease leading to undulant fever in humans and abortion in cattle. The immune response against this bacterium relies on the recognition of microbial pathogen-associated molecular patterns, such as lipoproteins, lipopolysaccharides and DNA; however, the immunostimulatory potential of B. abortus RNA remains to be elucidated. Here, we show that dendritic cells (DCs) produce significant amounts of IL-12, IL-6 and IP-10/CXCL10, when stimulated with purified B. abortus RNA. IL-12 secretion by DCs stimulated with RNA depends on TLR7 while IL-6 depends on TLR7 and partially on TLR3. Further, only TLR7 plays a role in IL-12 production induced by B. abortus infection. Moreover, cytokine production in DCs infected with B. abortus or stimulated with bacterial RNA was reduced upon pretreatment with MAPK/NF-κB inhibitors. By confocal microscopy, we demonstrated that TLR7 is colocalized with B. abortus in LAMP-1+ Brucella-containing vacuoles. Additionally, type I IFN expression and IP-10/CXCL10 secretion in DCs stimulated with bacterial RNA was dependent on TLR3 and TLR7. Our results suggest that TLR3 and TLR7 are not required to control Brucella infection in vivo but they play an important role on sensing B. abortus RNA in vitro.